2012
DOI: 10.5194/acp-12-11951-2012
|View full text |Cite
|
Sign up to set email alerts
|

Radical budget analysis in a suburban European site during the MEGAPOLI summer field campaign

Abstract: Chemical Ionisation Mass Spectrometer measurements of hydroxyl radical (OH) and the sum of hydroperoxy and organic peroxy (HO<sub>2</sub>+RO<sub>2</sub>) radicals were conducted during the MEGAPOLI summer field campaign at the SIRTA observatory near Paris, France, in July 2009. OH and (HO<sub>2</sub>+RO<sub>2</sub>) showed a typical diurnal variation with averaged daytime maxima values around 5&times;10<sup>6</sup> and 1.2&times;10<sup>8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 80 publications
(99 reference statements)
0
65
1
Order By: Relevance
“…The high OH + NO 2 reaction rate was mainly caused by the relatively high daily average NO x concentration during the study period, with a value of 44 ppbv. The reaction rate of HO 2 + NO in this study is lower than that reported by Liu et al [] (19.8 ppbv h −1 , in Beijing) and Michoud et al [] (10.9 ppbv h −1 , in France). The main reason for this discrepancy is that those two studies were performed during summer, when the photolysis rate is at its highest for the year.…”
Section: Resultsmentioning
confidence: 99%
“…The high OH + NO 2 reaction rate was mainly caused by the relatively high daily average NO x concentration during the study period, with a value of 44 ppbv. The reaction rate of HO 2 + NO in this study is lower than that reported by Liu et al [] (19.8 ppbv h −1 , in Beijing) and Michoud et al [] (10.9 ppbv h −1 , in France). The main reason for this discrepancy is that those two studies were performed during summer, when the photolysis rate is at its highest for the year.…”
Section: Resultsmentioning
confidence: 99%
“…In urban environments, measured HO 2 concentrations were sometimes found to agree with model predictions Emmerson et al, 2007; Published by Copernicus Publications on behalf of the European Geosciences Union. 96 M. M. Lew et al: Hydroperoxy radical in the atmosphere using laser-induced fluorescence 2009b; Michoud et al, 2012;Lu et al, 2013;Ren et al, 2013;Griffith et al, 2016), while other times the measurements were found to be both lower (George et al, 1999;Konrad et al, 2003) and higher than model predictions Ren et al, 2003;Emmerson et al, 2005;Kanaya et al, 2007a;Chen et al, 2010;Sheehy et al, 2010;Czader et al, 2013;Griffith et al, 2016). In forested environments, measured HO 2 concentrations were sometimes found to agree with model predictions (Tan et al, 2001;Ren et al, 2005Ren et al, , 2006 but were often found to be either lower (Carslaw et al, 2001;Kanaya et al, 2007bKanaya et al, , 2012Whalley et al, 2011;Mao et al, 2012;Griffith et al, 2013) or higher than model predictions (Carslaw et al, 2001;Kubistin et al, 2010;Kim et al, 2013;Hens et al, 2014).…”
Section: Introductionmentioning
confidence: 84%
“…FSNS is overpredicted over Europe (see Figure ), allowing more photolytic reactions to produce OH (e.g., photolytic reactions of O 3 and VOCs), and therefore more OH can oxidize NO 2 to produce HNO 3 . In addition, the observed surface OH concentrations vary from 0 to 6 × 10 6 molecules cm −3 , with a mean maximum value of 4.2 × 10 6 molecule cm −3 in summer over Europe [ Michoud et al ., ]. The summer (JJA) average of simulated OH over Europe is about 0.05–0.35 ppt (or 1–7 × 10 6 molecules cm −3 ), indicating possible OH overpredictions.…”
Section: Model Evaluation and Intercomparisonmentioning
confidence: 99%